Environment-Based Arabic Vocabulary Learning in Islamic Kindergarten - Muhammad Yusuf Salam; Adam Mudinilllah; Olivia Levan’s (STKIP Singkawang, 2022)
Over time the world evolved in all fields. One of them is in the areas affected by the evolution of the times, namely the field of education. Education should be flexible so that there is a synchronization between the development of the times and the world of education. More and more, we realize that there is a need for an innovative and competitive next generation, not only nationally but also internationally. Moving on from this, the researcher took the initiative to provide environment-based Arabic vocabulary material to students at the early childhood education level, namely Islamic Kindergartens. The purpose of this study was to test whether environmental-based Arabic vocabulary learning could be realized for students in Islamic Kindergartens. The method used in this research is the descriptive qualitative method by analyzing social events, phenomena or events. The research subjects are Al-Amin Islamic Kindergarten students whose address is at Jl. Ahmad Yani No. 89 D, Baringin, Five Peoples of Tanah Datar Regency, West Sumatra Province. In this study, researchers used the Spradley model of data analysis, namely domain analysis, by obtaining a general description of the researchers' observed events. The research was conducted for three days inside and outside the classroom. After the researchers observed, it can be concluded that the provision of environment-based Arabic vocabulary learning materials in Islamic Kindergartens can be realized by providing simple materials adapted to students' cognitive abilities.